Custom Learning Objects in mobile devices applied to teaching the correct use of gyms by fresh air (Impetus, 2021)
This article presents a diagnosis that outlines the impending need for tools that personalize and teach users the correct use of public outdoor gyms. It is about generating a technological platform that allows generating an application for mobile devices, based on a set of user characteristics (physical, pathological, habits), which allow teaching through learning objects, the convenience of using the available machines and the exercises that can be performed on them.